(untitled) (Journal of Medicine, 2010)
Cardiovascular disease is the most frequent cause of death in patient with diabetes. It is difficult to evaluate cardiovascular status of patients with diabetes because of complex symptomatology. NTproBNP, a split peptide from pro BNP molecule is a novel biomarker, released from cardiac myocytes in response to myocardial stretch, cardio vascular disease, endothelial dysfunction and heart failure. We aimed to test that is elevated NTproBNP levels associated with increased risk of cardiovascular disease in diabetes patients in comparison to matched control. Demographic, anthropometric measure, NT pro BNP, lipid profile, blood glucose were estimated and compared among angiographically proven cardiovascular disease patients with diabetes and healthy controls. Univariate and multivariate analysis were carried out to compare individual factor using t-Test, ANOVA and the inter group comparisons were done by using Bon ferroni Post Hoc test. Patients with type 2 diabetes were shown to have higher NTproBNP values (n=50, 1481.021±813.405) than control subjects (n=50, 23.562±23.395) (p <0.05). NTproBNP levels were independently related to diabetes after adjustment for age, sex, family history, smoking, obesity, blood pressure and lipid profile. Our data suggests that the secretion of NT pro BNP is increased in type II diabetes patients, suggesting association of diabetes and NTproBNP in cardio vascular disease with higher prevalence. Thus NTproBNP may serve as a screening tool to diagnose patients with type II diabetes with cardiovascular disease having complex symptomatology. Keyword: NTproBNP, Cardiovascular disease, Diabetes DOI:10.3329/jom.v11i1.4266 J Medicine 2010: 11: 33-38